Molecular cloning of rat obese cDNA and augmented gene expression in genetically obese Zucker fatty (fa/fa) rats. - Ogawa, Y (1995)
The obese (ob) gene has recently been isolated through a positional cloning approach, the mutation of which causes a marked hereditary obesity and diabetes mellitus in mice. In the present study, we isolated rat ob cDNA and examined the tissue distribution of the ob gene expression in rats. We also studied the gene expression in genetically obese Zucker fatty (fa/fa) rats. The rat ob gene product, a 167 amino acid protein with a putative signal sequence, was 96 and 83% homologous to the mouse and human ob proteins, respectively. Northern blot analysis using the rat ob cDNA probe identified a single mRNA species of 4.5 kb in size in the adipose tissue, while no significant amount of ob mRNA was present in other tissues in rats. The ob gene was expressed in the adipose tissue with region specificities. The rank order of the ob mRNA level in the adipose tissue was epididymal, retroperitoneal, and pericardial white adipose tissue > mesenteric and subcutaneous white adipose tissue > or = interscapular brown adipose tissue. The ob gene expression occurred in mature adipocytes rather than in stromalvascular cells isolated from the rat adipose tissue. Expression of the ob gene was markedly augmented in all the adipose tissue examined in Zucker fatty (fa/fa) rats at the stage of established obesity. The present study leads to the better understanding of the physiologic and pathophysiologic roles of the ob gene.